The Use of Al-Maslahah Al-Mursalah in The Ijtihad of Imam Ash-Shafi’i - Muhammad Hidayat Hidayat (Sufiya Journal of Islamic Studies, 2023)
This study aims to answer such debate in that whether Imam ash-Shafi’i accepted or did not accept al-maslahah al-mursalah as dalil hukm(legal argument), or theoretically he did not accept it, but accept it practically. In relation to such issue, this study follows descriptive analysis method with the following steps; a) collecting data regarding the meaning of al-maslahah al-mursalah so that it can be used in analyzing the application of Imam ash-Shafi’i Fiqh law, b). collecting data regarding Imam ash-Shafi’i legal thought from ar-Risalah, al-Umm and Ikhtilaf al-Hadith to reconstruct his legal thought so that his frame of mind and its relation to al-maslahah al-mursalah can be seen clearly, c) describing the issue of Fiqh obtained from the books of Imam ash-Shafi’i and other books which may be determined by Imam ash-Shafi’i based on al-maslahah al-mursalah, d) analyzing the data on the legal thoughts and Fiqh issue of Imam ash-Shafi’i, and comparing this with the theory of al-maslahah al-mursalah so that it can be analyzed whether Imam ash-Shafi’i used al-maslahah al-mursalah or not, and e) drawing conclusions. The results of this study conclude that Imam ash-Shafi’i used al-maslahah al-mursalah as the basis or argument in establishing the Fiqh law. However, the al-maslahah al-mursalah is not a stand-alone argument because al-maslahah al-mursalah is included in the ijtihad pattern of Imam ash-Shafi’i which is called Qiyas.